Double J ureteral stent removal following pediatric laparoscopic pyeloplasty without cystoscopy - Edit Kecskés; Levente Szabó; Gábor Varga; László Sasi Szabó (Elsevier, 2024)
Background: Double J ureteral stents (DJUS) require anesthesia and cystoscopy for its removal. We analysed the effectivity of a noncystoscopy (NC) DJUS removal procedure in vivo described by Shao. The study aimed to determine whether this method can safely be applied in our practice. Methods: We analysed the data of all pediatric patients who had noncystoscopy DJUS removal following laparoscopic pyeloplasty in our Department between January 2021- December 2023 and compared data from cystoscopic (CS) interventions in 2020. We examined the success and complication rate of the in vivo intervention and its cost-effectivity. Ex-vivo bladder models were used to study the success rates of DJUS removal under different conditions and the impact of suture positioning. Results: After laparoscopic pyeloplasty 34 NC and 10 CS stent removals were performed. The mean age was 35.65 months (NC) vs. 67.6 months (CS). DJUS removal was successful after an average of 2.08 trials without perioperative complications. Intervention time was significantly shorter in NC (4.62 mins vs. 12.90 mins, p<0.005). Noncystoscopic removal reduces hospital material costs (NC: ∼ 8.4 EUR vs. CS: ∼ 98 EUR). In the ex-vivo bladder model, 400 attempts were made to remove the stent. The success rate was higher in the empty model (38.5% vs. full: 32%, p = 0.21). The position of the suture did not significantly affect the success rate (37% vs. 33.5%, p= 0.53). Conclusions: This innovative technique proved to be safe and effective. NC removal significantly shortens procedural time, is less burdensome for the patient and reduces hospital material costs.